Sirolimus therapy for kaposiform hemangioendothelioma with long‐term follow‐up. Issue 11 (5th September 2019) - Wang, Zuopeng; Yao, Wei; Sun, Hongqiang; Dong, Kuiran; Ma, Yangyang; Chen, Lian; Zheng, Shan; Li, Kai
Abstract: Mammalian target of rapamycin inhibitors have shown promising results in the management of kaposiform hemangioendothelioma (KHE). The purpose of this study was to present our experience involving sirolimus therapy for KHE. A retrospective study was conducted to review the medical documents of 26 patients with KHE who were treated with sirolimus at our hospital between March 2012 and December 2016. Fifteen males and 11 females manifested KHE in infancy with an average age of 2.9 ± 1.8 months. Multiple anatomical sites were involved. Four patients had multifocal lesions, while 22 patients had solitary lesions. Twenty‐five patients had Kasabach–Merritt phenomenon (KMP). Twenty patients completed sirolimus therapy in 28.3 ± 12.5 months. Nineteen KHE lesions reduced to small residuals with platelet counts reaching normal levels 3.7 ± 2.8 weeks after treatment; one KHE lesion had no response to therapy. One patient with multifocal lesions died due to a severe infection, although the patient had previously responded to sirolimus. Five patients remained in treatment and had good responses with normal platelet counts. Nineteen patients with anemia had normal hemoglobin levels after 3.5 ± 1.9 weeks of treatment. Mild side effects were observed. The median follow‐up time was 32 months (26–60 months), with no evidence of recurrences. Sirolimus was shown to be efficacious in the management of KHE with an average course of 28 months. The time‐to‐response was variable, with an average of 1 week. After 4 weeks of treatment, the platelet count and hemoglobin level had normalized. Multifocal KHE with KMP is more severe than solitary KHE.